Design and Implementation of Blind Runner Guide Android Mobile Application for the Visual Impairment User Experience - Andrie Asmara, Rosa; Al Huda, Fais; Nur Handayani, Anik (International Journal of Engineering and Technology, 2018)
Visual Impairment persons have the disadvantage when they try to walk straight without any active or passive guidance. They usually tend to walk with circle path how hard they try, this is called veering behavior and it is nature in human instinct. For walking, most visual impairment persons will use at least a support cane for their walking guidance. In Running Athletics para-competition, visual impairment athletes did not use a support cane, they will use human assistant and run together beside them. The athletes will hold tether where the other end were held by the assistant, whose called sighted guide. Some visual impairment school in Indonesia have some difficulties to train their runner athletes, one of them is the limitation of human running assistant provide by them. Blind Runner Guide Android Mobile Application offering one great feature for the visual impairment persons. This application will assist users to stay straight during their walk or run. This application still however can only be used for straight run competition, not circle athletic path which is usually used in international standard competition. This paper review the Visual Impairment user experiences using the application. From the experiment results shows that the application could reduce more than 50% percent of veering behavior. Experiment results from the short version UEQ shows 1.625 mean pragmatic quality score (good benchmark), 0.625 hedonic quality score (bad benchmark), and 1.17 overall quality score (above average benchmark).Â Â